Knowledge Management Initiative Framework for Higher Education Institutions: Nepalese Experiences - Shrestha, Prakash; Chhetri, Guna Raj (AMC Journal, 2024)
The purpose of this research is to develop a knowledge management (KM) initiative framework for Nepalese higher educational institutions (HEIs). It takes into account both a descriptive and analytical approach. This study is based on a questionnaire survey of 105 Nepalese authorities and academicians from 21 HEIs. The findings indicate that the core functions of KM initiatives are the teaching-learning atmosphere, research works and projects, the use of modern technology, and the use of knowledge-based systems. Inappropriate institutional culture, lack of knowledge sharing practice, lack of use of contemporary technology, reuse of old knowledge, traditional technique of KM, reluctant to change an existing habit, lack of institutional efforts to create knowledge, poor motivation and enhancement practice for creating and utilizing knowledge, insufficient capture of process and legacy knowledge, and lack of funding for classroom preparation, library management, laboratories, and information technology are key the challenges. Knowledge flow and transfer, resource persons, and their expertise, consideration of the knowledge needed by stakeholders, making the understanding visible, the institutionalization of KM-related policy, and investment in infrastructure development are the fundamentals for implementing KM initiatives in HEIs of Nepal.